2022
DOI: 10.1136/bmjopen-2021-058626
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative study exploring lessons from Liberia and the UK for building a people-centred resilient health systems response to COVID-19

Abstract: IntroductionCOVID-19 has tested the resilience of health systems globally and exposed existing strengths and weaknesses. We sought to understand health systems COVID-19 adaptations and decision making in Liberia and Merseyside, UK.MethodsWe used a people-centred approach to carry out qualitative interviews with 24 health decision-makers at national and county level in Liberia and 42 actors at county and hospital level in the UK (Merseyside). We explored health systems’ decision-making processes and capacity to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…However, some communication gaps were also identified; for example, a lack of communication aligned with rapidly changing protocols that increased the difficulty of remaining informed [ 56 ]. Challenges included a lack of intra-and inter professional communication between other units [ 56 ], a lack of access to technology and inconsistent information [ 81 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some communication gaps were also identified; for example, a lack of communication aligned with rapidly changing protocols that increased the difficulty of remaining informed [ 56 ]. Challenges included a lack of intra-and inter professional communication between other units [ 56 ], a lack of access to technology and inconsistent information [ 81 ].…”
Section: Resultsmentioning
confidence: 99%
“…It was clear from the included studies that navigating the challenges of the COVID-19 pandemic, which came with the need to constantly learn and make adaptations in response to unexpected variation and changes, came at a personal cost to healthcare workers, particularly to those at the frontlines of care. Nine (18%) of the included studies reported that the increased workload and strenuous work conditions had negative physical consequences on healthcare workers [ 54 , 56 , 61 , 67 – 69 , 79 , 81 , 82 ]. For example, nurses reported increased “tiredness”, “exhaustion”, “muscle weakness” and “loss of appetite”, during the pandemic as a result of working longer shifts, often without breaks, while being “weighed down by PPE equipment” [ 67 , 69 ].…”
Section: Resultsmentioning
confidence: 99%
“…Findings from the current study highlight important lessons for optimal delivery of routine essential services in the ongoing COVID-19 response and future shocks. These are aligned with the people-centred approach and have been outlined in two separate policy briefs focusing on Liberia [42] and Merseyside [43]. Notably, they suggest the need for pandemic responses to be informed by equity considerations, including tackling immediate pandemic-related and established structural barriers to care [44].…”
Section: Discussionmentioning
confidence: 99%
“…A collective case study approach involving simultaneous exploration and comparison of the experiences in Liberia and in Merseyside, UK was adopted to gain perspectives on health system responses in both low-and high-income contexts [23,24]. The study was guided by a people-centred health systems resilience framework [25], adapted from existing resilience models [26][27][28] (Fig. 1).…”
Section: Study Design and Conceptual Frameworkmentioning
confidence: 99%
See 1 more Smart Citation